(untitled) - Abramson, Ann (New York, 2007)
Looks closely at Anne Frank's life before the secret annex, what life was like in hiding from the Nazis, and the legacy of her diary.
Keywords: Jews,Người Do Thái; Biography,Tiểu sử; Văn học vị thành niên; Netherlands,Hà Lan